2019
DOI: 10.17159/sajs.2019/6028
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall and river flow trends for the Western Cape Province, South Africa

Abstract: Climate change has the potential to alter the spatio-temporal distribution of rainfall, subsequently affecting the supply and demand of water resources. In a water-stressed country such as South Africa, this effect has significant consequences. To this end, we investigated annual and winter rainfall and river flow trends for the Western Cape Province over two periods: 1987–2017 and 1960–2017. Annual rainfall for the most recent 30-year period shows decreasing trends, with the largest magnitude of decrease at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…If this was the case, changes in rainfall regimes could impact our predictions, because our population projections considered a scenario where future rainfall remains at levels observed during the study period (2008–2019). Climate analyses suggest that the rain season might be shortening in the Western Cape of South Africa and that the total rain might be decreasing [ 50 , 51 ], which could result in a steeper population reduction than anticipated by our model.…”
Section: Discussionmentioning
confidence: 99%
“…If this was the case, changes in rainfall regimes could impact our predictions, because our population projections considered a scenario where future rainfall remains at levels observed during the study period (2008–2019). Climate analyses suggest that the rain season might be shortening in the Western Cape of South Africa and that the total rain might be decreasing [ 50 , 51 ], which could result in a steeper population reduction than anticipated by our model.…”
Section: Discussionmentioning
confidence: 99%
“…These findings collaborate with various research conducted in the WC and EC provinces. For instance, studies by Lakhraj-Govender and Grab [56] reported a decreasing trend in annual and winter rainfall and river flow in the WC province for the period spanning from 1987 to 2017. Similar studies focusing on rainfall characteristics have been reported by Botai et al [10] in the WC, Botai et al [22] in the EC and Mahlalela et al [57] in the Southwestern Cape regions.…”
Section: Discussionmentioning
confidence: 99%
“…According to [1], climate change is possibly the biggest environmental problem facing the globe. Masereka et al [2] stated that flood risks are caused by extreme rainfall events that have resulted in flood disasters that accounted for about 47% of all weather-related calamities, affecting 2.3 billion people worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The climate of South Africa ranges from desert and semi-desert in the dry north-western region to sub-humid and wet along the eastern coastal area [8]. According to [1], South Africa is a water-stressed country with high spatio-temporal rainfall variability. This climate variability in South Africa is a result of the location of South Africa in the tropical and subtropical zones.…”
Section: Introductionmentioning
confidence: 99%